Pre- performance routines followed by free throw shooting accuracy in secondary basketball players - Phelps Ashley; Kulinna Pamela (Sciendo, 2015)
Study aim: The purpose of the current study was to determine whether existing pre-performance routines had an effect on free throw shooting accuracy in high school pupils as compared to shooting without a pre-performance routine.